GOLD IS EARNED FROM THE PRODUCTION OF THAI GOLD LEAF - Dirk Bax (Indonesian Journal of Chemistry, 2001)
Thai people like to cover sacred objects or things dear to them with gold leaf.. Statues of Buddha are sometimes covered with so many layers of gold leaf that they become formless figures, that can hardly be recognized. Portraits of beloved ancestors, statues of elephants and grave tombs are often covered with gold leaf. If one considers the number of Thai people and the popularity of the habit, the amount of gold involved could be considerable.